2021
DOI: 10.1182/bloodadvances.2021004862
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of allosensitized patients receiving allogeneic transplantation

Abstract: Donor-specific anti-HLA antibodies (DSA) are a major cause of engraftment failure in patients receiving haploidentical stem cell transplantation (HaploSCT). Effective treatments are needed for these patients who often have no other donor options and/or are in need to proceed urgently to transplantation. We studied a multimodality treatment with alternate day plasma exchange, rituximab, intravenous gamma globulin (IvIg) and an irradiated donor buffy coat for patients with DSA at two institutions. Thirty-seven p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 35 publications
1
18
0
2
Order By: Relevance
“…All patients received PTCy-based GVHD prophylaxis with tacrolimus and mycophenolate, as previously described by our group ( 34 ). Patients with a high level (mean fluorescence intensity >2,000) of donor-specific anti-HLA antibodies received desensitization therapy before HSCT per institutional protocol ( 35 ). Comorbidities before HSCT were evaluated using the Hematopoietic Cell Transplant-Comorbidity Index (HCT-CI) ( 36 ) and hematologic malignancies were risk-stratified using the refined Disease Risk Index (DRI) ( 37 ).…”
Section: Methodsmentioning
confidence: 99%
“…All patients received PTCy-based GVHD prophylaxis with tacrolimus and mycophenolate, as previously described by our group ( 34 ). Patients with a high level (mean fluorescence intensity >2,000) of donor-specific anti-HLA antibodies received desensitization therapy before HSCT per institutional protocol ( 35 ). Comorbidities before HSCT were evaluated using the Hematopoietic Cell Transplant-Comorbidity Index (HCT-CI) ( 36 ) and hematologic malignancies were risk-stratified using the refined Disease Risk Index (DRI) ( 37 ).…”
Section: Methodsmentioning
confidence: 99%
“…DSA desensitization with daratumumab has been described in solid-organ transplant recipients and in an HLA-mismatched HCT recipient. 5,6,9,11 Interestingly, after receiving daratumumab, patient 5 became negative for C1q-fixing antibodies, which likely improved her prognosis. 4 Although frequent blood product transfusion may be unavoidable, an effort should be made to limit exposure by minimizing both the number and volume of blood products or by choosing platelet units that do not expand sensitization to prevent DSA development.…”
Section: Society Of Blood and Marrow Transplantation Further Recommendsmentioning
confidence: 99%
“…Chang et al [ 51 ] suggested that high DSA levels were associated with primary engraftment failure and poor primary engraftment in HLA haploidentical transplantation. Ciurea et al [ 52 ] used plasma exchange, rituximab, intravenous immunoglobulins, and irradiated donor buffy coat to intervene in patients with high DSA levels and found that the engraftment success rate was higher in patients with decreased DSAs and negative complement component 1q. Pretreatment protocols can also affect the engraftment success rate.…”
Section: Hematopoietic Reconstitution After Bone Marrow Transplantationmentioning
confidence: 99%